Heavy metal geochemistry of contaminated fenland soils in NW England - Atkinson, Nikola R. (2010)
The use of peri-urban fenlands for agriculture usmg urban waste as manorial treatments is increasingly common worldwide, particularly in developing countries. The risk to human health from the use of these contaminated materials for crop production has been studied using two historically contaminated fenlands in NW England. The GBASE survey carried out by the British Geological Survey identified two areas of metal contaminated fenland; west of Manchester (Chat Moss) and north of Liverpool (Halsall Moss). The two areas are used for arable agriculture, and current demand for locally sourced food is increasing pressure on farmers to move to vegetable horticulture. The effect of the metal contamination on the soils and crops is of key importance to monitor any risk to the food chain. Historical research identified the two mossland areas as contaminated with urban wastes, Halsall Moss contaminated with urban organic wastes such as manure and Chat Moss contaminated with urban organic and mineral wastes. Waste disposal on Chat Moss was carried out by the Manchester Corporation to dispose of city waste and generate farmland from the peat. During the drainage up to 1.92 Mt of waste was incorporated into the soil, representing 38% of the topsoil today. Profiles of contaminated and control sites on Chat Moss and a contaminated site on Halsall Moss were collected, with pH, organic matter content and trace metal content measured. Trace metal content was elevated over subsoil levels in the topsoil of all sites, for example arsenic showed topsoil concentrations of 45 mg kg-I in the most contaminated site (CM-3) compared to 3 mg kg-I in the subsoil. The elevation of trace metals in the historically uncontaminated sites indicated possible atmospheric deposition of metals at the control site. Contamination levels were found to be less than originally identified in the GBASE survey, possibly due to differing sample preparation methods and survey size. The GBASE survey measured an average lead concentration in contaminated sites of 1985 mg kg-I compared to 378 mg kg-I measured by the current study. Arsenic and cadmium concentrations exceeded Soil Guideline Values in the most contaminated site, 43 mg kg-I and 1.8 mg kg-I respectively, but all other metals were within guideline limits. Halsall Moss was found to be less contaminated than Chat Moss, due to the mainly organic nature of the waste disposed at Halsall Moss. The mobility and fractionation of the contamination at the most contaminated site on Chat Moss were studied to understand the behaviour of the metals and assess potential risk to ecological or human health. Using sequential extractions, most metals were identified as hosted by organic, Fe/Mn oxide or residual phases. There was no difference observed in fractionation between control and contaminated sites, indicating that soil properties such as organic matter and Fe/Mn oxide content were more important in controlling fractionation than the source of metals. A comparison of Chat Moss with three soils of known contamination history also identified soil properties as key in controlling fractionation. Lability of Pb in the contaminated Chat Moss soil was assessed using 204Pb stable isotope dilution, it was found that 65% of lead was labile. This was the highest out of the four soils studied, and again most likely controlled by soil properties such as organic matter content and pH. The impact of flooding events on the Chat Moss soils was assessed, and it was found that under redox conditions of -200 mY, large quantities of arsenic, lead, molybdenum and manganese were released to soil solution, and drinking water limits for these metals were violated, for example As solution concentration reached 308 J.1g L-1 and the drinking water limit is 10 Ilg L-1. Environmental quality standards for freshwater were also violated by arsenic, copper, lead and zinc showing potential ecological hazard under these reducing conditions, with lead concentrations reaching 137 J.1g L-1 in contrast to the environmental quality standard of 4 - 20 J.1g L-1. The effect of soil contamination on vegetables grown on Chat Moss was also investigated, EU limits for Cd were exceeded by lettuce and onion, and EU limits for Pb were exceeded by parsley, carrot, radish and onion. Hazard Quotients used to assess the impact of plant contamination in the context of human intake showed that only cadmium and molybdenum were potentially hazardous. Thus it is not recommended to grow lettuce (high Cd), parsley, cabbage, radish and onion (all high molybdenum) at contaminated sites on Chat Moss. To minimise risk, conducting liming to raise the pH and immobilise the metals could be used, and careful selection of cultivars that do not accumulate metals is recommended.